Species of the Tribe Lamiini (Coleoptera: Cerambycidae) from the Reserva Biológica Alberto Manuel Brenes, San Ramón, Costa Rica - Esteban-Duran, J. R.; Salazar-Rodriguez, A. H.; Gonzalez-Nuñez, M.; del Estal-Padillo, P.; Castresana-Estrada, L. (Spanish Journal of Agricultural Research, 2010)
The knowledge of present species in protected areas has a great interest in order to estimate their biodiversity. In this work, we collected samples of the tribe Lamiini (Coleoptera: Cerambycidae) in the Reserva Biológica Alberto Manuel Brenes, San Ramón, Costa Rica. Eleven species of Lamiini were identif ied:Plagiohammus albatus, Plagiohammus elatus, Plagiohammus emanon, Plagiohammus rubefactus, Plagiohammus spinipennis, Deliathis nivea, Deliathis quadritaeniator, Neoptychodes cretatus, Ptychodes politus lecontei, Taeniotes praeclarus, Taeniotes scalatus and Taeniotes xanthostictus. Two of these (P. albatus and P. elatus) are new for the studied area. Figures, descriptions, collection dates and their abundance level are provided from each identified species.